Behavioral Determinants of Balipay E-Wallet Adoption among Generation Z - Ketut Tanti Kustina; Kadek Mela Kusuma Dewi; Ni Luh Putu Sariani (Universitas Warmadewa, 2026)
This study examines how financial literacy and perceived ease of use shape Generation Z’s e-wallet adoption of the Balipay e-wallet, and whether financial behavior mediates these relationships. Data were collected from 100 Balipay users in Denpasar City using a structured questionnaire. The research model was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS to test both direct and indirect effects. Results indicate that financial literacy, perceived ease of use, and financial behavior significantly have positive effects on e-wallet adoption of Balipay. In addition, financial literacy and perceived ease of use significantly enhance financial behavior, which partially mediates their effects on e-wallet adoption. From a practical perspective, the findings suggest that Balipay providers and local stakeholders should integrate user-friendly interface design with targeted financial education programs to encourage responsible and sustained e-wallet adoption among young users. Future studies may compare Balipay with other e-wallet brands and expand the sample beyond Denpasar to improve the external validity of the findings.